Constructing a conceptual framework: interpreting visual preference and visual pollution factors among viewers in highway landscapes - Gao, Hangyu; Bakar, Shamsul Abu; Suhardi, Maulan; Guo, Yu (Elsevier, 2025)
Highway landscapes play a multifaceted role in modern infrastructure, providing environmental mitigation and cultural expression while impacting viewers’ experiences and well-being. However, these landscapes face challenges from visual pollution, which can compromise their aesthetic appeal and functionality. This study proposes a comprehensive conceptual framework that addresses gaps in current visual impact assessment methodologies, particularly in systematically capturing how viewers interpret and respond to visual pollution in highway landscapes. While NCHRP (NATIONAL COOPERATIVE HIGHWAY RESEARCH PROGRAM) Report 741 established evaluation criteria and FHWA (Federal Highway Administration) Guidelines offered procedural guidance, neither fully addresses the complex relationship between visual pollution and viewer perception. Our framework integrates multiple environmental theories with landscape character assessment principles, identifying land use, landform, and land cover as fundamental elements and seven visual perception variables (openness, naturalness, complexity, coherence, legibility, mystery, and imageability). This integration provides explicit connections between theoretical foundations and assessment variables, enabling a more informed evaluation of visual pollution impacts. The framework's methodological innovation includes a two-stage assessment process and incorporates socioeconomic considerations previously lacking in existing approaches. Despite geographical and cultural limitations, this framework offers valuable guidance for highway planners, designers, and policymakers in creating more sustainable and aesthetically pleasing environments. Future research directions include developing quantitative metrics, implementing studies across diverse environments, and exploring cultural adaptations of the framework.